New trends and hotspots in sepsis-related protein post-translational modification: a bibliometric and visual analysis - Song, Lin; Ma, JingYi; Jiang, Wei; Liu, Ke; Wang, Jing; Lin, Hua; Yu, Jiangquan; Zheng, Ruiqiang (Frontiers in Medicine, 2025)
BackgroundSepsis is a clinical syndrome characterized by high morbidity and mortality rates, posing a severe threat to human health. Its pathophysiology is complex, involving multiple physiological and pathological processes. Protein post-translational modification (PTM) play a pivotal role in the pathophysiology of sepsis by regulating inflammation, immune responses, and organ dysfunction. In recent years, there has been a growing focus on the association between sepsis and PTM; however, a comprehensive and systematic analysis of the current research status and development trends in this field is still lacking.MethodsThis study analyzed literature from the Web of Science Core Collection published between 2005 and 2024. CiteSpace, VOSviewer, and Excel facilitated the bibliometric analysis, visualizing publication trends, contributions across countries/regions and institutions, journal distributions, author collaboration networks, and keyword clusters.ResultsA total of 1705 articles were included, originating from 58 countries/regions. The annual publication volume showed exponential growth (R2 = 0.9662), with China leading the way (48.68%), followed by the United States (29.27%). Shanghai Jiao Tong University emerged as a high-yield institution (n = 51), while the University of Pittsburgh demonstrated the highest citation impact (with an average of 109.87 citations per article). Prominent journals featuring these articles include Shock (n = 77) and the Journal of Immunology (with an average citation of 65.75 times per article). Research hotspots were centered around phosphorylation, ubiquitination, and methylation, with emerging trends such as sepsis-associated acute kidney injury (SA-AKI), autophagy, and mitochondrial dysfunction.ConclusionResearch on the sepsis-related PTM is flourishing. This study systematically reveals the research dynamics and core trends in this field.